Investigation of factors that influence collaboration within an online learning context. (1st January 2011) - Geng, Gretchen
The purpose of the paper was to identify the factors that influence collaborative online learning. The findings showed that the collaborative online learning assisted in students' achievement in successful online learning. The findings of the study indicated that students possessed remarkably clear views as to the nature of the pedagogical support from teachers, assistance from other successful students, and other factors that influenced their online learning results. Online teachers and students may find these results useful in enhancing the effectiveness of online teaching and studying.